Indian education through a G20 lens-Ensuring continuity of sustainable development - Kushwaha, Ravindra K.; Patel, Sonia; Ahmad, Sarfaraz (The Scientific Temper, 2023)
Beginning with a global inquiry for increasing technology-enabled learning and education, this article analyses Indian education policy responses in G20 nations. Educators and students in India are generally well-prepared to use best practices in tech-related education. Therefore, the G20 partnership must think about how to best encourage the development of educational systems and practices that are robust, efficient, equitable, and adaptive in order to better respond to and lessen the effects of current and future crises (United Nations 2020a; Reimers and Schleicher 2020). In this context, it is currently necessary to make provisions to improve access to the technology infrastructures for remote education within and outside the G20 countries. Additionally, to facilitate safer and more fluid transitions to remote modes of EduTech during school education in India is disrupted, educators, students, and parents require help and direction. Finally, the G20 must immediately look into more sustainable growth models in case the education sector experiences long-term difficulties.